2017
DOI: 10.2147/ceor.s127097
|View full text |Cite|
|
Sign up to set email alerts
|

Budget impact analysis of the simplification to atazanavir + ritonavir + lamivudine dual therapy of HIV-positive patients receiving atazanavir-based triple therapies in Italy starting from data of the Atlas-M trial

Abstract: BackgroundThis analysis aimed at evaluating the impact of a therapeutic strategy of treatment simplification of atazanavir (ATV)+ ritonavir (r) + lamivudine (3TC) in virologically suppressed patients receiving ATV+r+2 nucleoside reverse transcriptase inhibitors (NRTIs) on the budget of the Italian National Health Service (NHS).MethodsA budget impact model with a 5-year time horizon was developed based on the clinical data of Atlas-M trial at 48 weeks (in terms of percentage of patients experiencing virologic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…If dual regimes are going to be proved non-inferior to triple combination therapy in the ART-naïve population, a single tablet of this dual regimen will likely be developed. Thus, as a consequence of the publication of the results of these studies, in order to save toxicities and resources, we could see a shift in drug production and clinical use of dual therapies [ 12 , 13 ]. However, it has been recently shown that virological suppression and CD4 cell count fail to protect from the major causes of death of persons living with HIV (PLWHIV), which are mainly non-AIDS-related events, also known as serious non-AIDS events (SNAEs) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…If dual regimes are going to be proved non-inferior to triple combination therapy in the ART-naïve population, a single tablet of this dual regimen will likely be developed. Thus, as a consequence of the publication of the results of these studies, in order to save toxicities and resources, we could see a shift in drug production and clinical use of dual therapies [ 12 , 13 ]. However, it has been recently shown that virological suppression and CD4 cell count fail to protect from the major causes of death of persons living with HIV (PLWHIV), which are mainly non-AIDS-related events, also known as serious non-AIDS events (SNAEs) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over a 3-year period, ART cost decreased between € 23.1 million and € 44.3 million considering different scenarios. A third analysis was conducted to evaluating the impact of treatment simplification of atazanavir (ATV) + ritonavir (r) + lamivudine (3TC) in virologically suppressed patients receiving ATV + r + 2 nucleoside reverse transcriptase inhibitors (NRTIs) [10]. The perspective of the Italian National Health Service (NHS) was considered.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the availability of more potent drugs with a high genetic barrier [17] has renewed the interest for simpler HIV regimens. Several drugsparing strategies have been investigated both in ART-naïve patients and, more extensively, in virologically suppressed patients receiving three-drug regimens, in order to achieve and maintain viral suppression and immunological control, improving tolerability, and adherence, and limiting at the same time pill burden and costs [18].…”
Section: Introductionmentioning
confidence: 99%